Stochastic simulations of a macroeconomic disequilibrium model for West Germany - Martin Schellhorn; Peter Winker (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1994)
In this paper a macroeconometric disequilibrium model for West Germany is presented and its quality for policy simulations and forecasting are analyzed using stochastic in-sample simulations. The model is built on a dynamic disequilibrium model of firms' behaviour. Due to delayed adjustment of production inputs, and sluggish adjustment of wages and prices, a market disequilibrium can arise on labour and goods micro markets. Aggregation leads to an explicit functional form for aggregate transactions on labour and goods markets dependent on aggregate supply, demand, and mismatch. The empirical application of the model confirms that underutilization of labour and capital are important phenomena. Shares of firms facing different constraints on the goods and labour market can be derived from the model. These proportions changed considerably during the last three decades. Some deterministic simulations of different shocks affecting the economy including fiscal and monetary shocks, and migratory movements showed a strong influence of the prevailing rationing regime on the outcomes. The robustness of these results is assessed using stochastic in-sample simulations for the period 1981-1988. Simulations using stochastic errors for the model's 23 estimated equations help to evaluate the effects of non-linearities and dynamic features on the forecasting quality of the model. Furthermore, a comparison between deterministic and different stochastic simulations allows the conclusion to be drawn that notwithstanding the non-linearities and dynamic features the Simulation properties of the model are reasonable in general.
Keywords: 330; Ökonometrisches Makromodell; Neukeynesianische Makroökonomik; Simulation; Deutschland